Effect of Different Compatibilization Systems on the Rheological, Mechanical and Morphological Properties of Polypropylene/Polystyrene Blends - Martina Seier (Polymers, 2020)
The influence of reactive processing, non reactive and reactive copolymers on immiscible polypropylene (PP)–polystyrene (PS) blends with varying PS concentrations (10 wt.% and 25 wt.%) was evaluated by mechanical (tensile and tensile impact), rheological (melt flow rate, extensional and dynamic rheology) and morphological (scanning electron microscopy) analysis. As an extended framework of the study, the creation of a link to industrial applicable processing conditions as well as an economically efficient use of compatibilzing agent were considered. For radical processed blends, a high improvement in melt strength was observed while non reactive copolymers exhibited a pronounced increase in toughness and ductility correlated with overall best phase homogeneity. Conversely, the influence of the reactive copolymer was quite different for the varied PS concentrations not allowing the assumption of a specific trend for resulting blend properties, but nevertheless in the case of a lower PS concentration the tensile impact strength exceeded the value of virgin PP. Since PS and PP are widely used, the findings of this work could not only be relevant for the generation of more versatile blends compared to virgin components but also for recycling purposes, allowing the enhancement of specific properties facilitating the production of more valuable secondary materials.